Policy and Planning for Regional Development in the North Coast of Central Java: A Review - Latue, Philia Christi; Rakuasa, Heinrich; Manakane, Susan. E (Nusantara Journal of Behavioral and Social Science, 2023)
Indonesia's coastal areas have abundant natural resources that need to be preserved in a planned manner. The implementation of development in a region has a different portion that causes an imbalance of economic activities in the region where the concentration of population in the coastal area has a diversity of service facilities and services. Coastal communities, especially those who work as fishermen, are closely related to poverty which is related to complex problems, where the cause is inequality of access and resources. The purpose of this research is to analyze the development of the region and the perceptions of relevant stakeholders so that it can be expected to formulate directions for the development of coastal areas in poverty reduction. The method used is a scalogram analysis to see the level of development of an area based on the completeness of infrastructure. The results of the analysis show that area IV (Karimunjawa Sub-district) is a priority area for coastal development. This is because the availability of infrastructure is a top priority in planning the development of an area. Poverty alleviation in coastal areas is carried out by community empowerment methods based on the potential of community character by changing the mindset in finding work so that it can generate sustainable income. Abstrak: Wilayah pesisir Indonesia memiliki sumber daya alam yang melimpah yang perlu dijaga kelestariannya secara terencana. Pelaksanaan pembangunan di suatu wilayah memiliki porsi yang berbeda sehingga menyebabkan ketidakseimbangan kegiatan ekonomi di wilayah tersebut dimana pemusatan penduduk di wilayah pesisir memiliki keragaman fasilitas pelayanan dan jasa. Masyarakat pesisir khususnya yang berprofesi sebagai nelayan sangat erat kaitannya dengan kemiskinan yang terkait dengan permasalahan yang kompleks, dimana penyebabnya adalah ketimpangan akses dan sumber daya. Tujuan dari penelitian ini adalah untuk menganalisis perkembangan wilayah dan persepsi stakeholder terkait sehingga diharapkan dapat merumuskan arahan pengembangan wilayah pesisir dalam penanggulangan kemiskinan. Metode yang digunakan adalah analisis skalogram untuk melihat tingkat perkembangan suatu wilayah berdasarkan kelengkapan infrastruktur. Hasil analisis menunjukkan bahwa wilayah IV (Kecamatan Karimunjawa) merupakan wilayah prioritas pengembangan wilayah pesisir. Hal ini dikarenakan ketersediaan infrastruktur menjadi prioritas utama dalam perencanaan pembangunan suatu wilayah. Pengentasan kemiskinan di wilayah pesisir dilakukan dengan metode pemberdayaan masyarakat yang berbasis pada potensi karakter masyarakat dengan merubah pola pikir dalam mencari pekerjaan sehingga dapat menghasilkan pendapatan yang berkelanjutan.